Fast ambipolar integrated circuits with poly(diketopyrrolopyrrole- terthiophene) - Roelofs, W. S. Christian; Mathijssen, Simon G. J.; Bijleveld, J. C.; Raiteri, D.; Geuns, T. C. T.; Kemerink, Martijn; Cantatore, E.; Janssen, René A. J.; Leeuw, Dago M. de (Applied physics letters, 2011)
Ambipolar integrated circuits were prepared with poly(diketopyrrolopyrrole-terthiophene) as the semiconductor. The field-effect mobility of around 0.02 cm2/V s0.02 cm2/V s0.02<mtext> </mtext><mtext>cm</mtext>2/<mtext>V</mtext><mtext> </mtext><mtext>s</mtext> for both electrons and holes allowed for fabrication of functional integrated complementary metal-oxide semiconductor (CMOS)-like inverters and ring oscillators. The oscillation frequency was found to have a near quadratic dependence on the supply bias. The maximum oscillation frequency was determined to be 42 kHz, which makes this ring oscillator the fastest CMOS-like organic circuit reported to date.